Media Edukasi Berbasis Aplikasi terhadap Kemampuan Ibu Menyusui - Surtania Surtania; Anggorowati Anggorowati; Achmad Zulfa Juniarto (Journal of Telenursing (JOTING), 2023)
This study examines research results in the last ten years on the effect of application-based educational media on mothers' breastfeeding ability. The method used in this literature review is to search for several articles through Pubmed, Proquest, Scopus, Science Direct, and Google Scholar. The results showed that the application of media in breastfeeding education could increase mothers' knowledge, attitudes, and skills in breastfeeding compared to ordinary care. The use of applications as educational media has ease in accessing information; it can be done anytime and anywhere. In conclusion, application-based educational interventions have proven effective in improving mothers' breastfeeding ability. Keywords: Application, Breastfeeding Ability, Educational Media